Tristan10M detector: characterization of a large area detector for time resolved experiments based on Timepix3 chip. (1st July 2022) - Chen, Z.; Crevatin, G.; Horswell, I.; Spiers, J.; Omar, D.; Williams, S.; Tartoni, N.
Abstract: Tristan10M is a 10-million-pixel large area detector based on the Timepix3 ASIC. The Timepix3 ASIC can work in event driven mode in addition to the standard frame based mode. Thanks to these capabilities of the Timepix3 ASIC, the Tristan detector is ideal for time-resolved experiments. The Tristan 10M detector is organized in a 2 × 5 module matrix, each module being made up of sixteen Timepix3 chips bump-bonded to a monolithic pixelated silicon sensor. In this contribution, we will report on the status of the detector development, and characterization results in terms of threshold equalization, energy calibration, and flat-field correction. A number of initial commissioning experiments have been carried out on the small molecule single crystal diffraction beamline I19 at Diamond light source, which we will also report on here. In particular, X-ray powder diffraction from a standard sample, LaB6, was performed to evaluate the inter-module alignment based on per-module basis.